2004
DOI: 10.1051/0004-6361:20034336
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear ring in the unbarred galaxy NGC 278: Result of a minor merger?

Abstract: Abstract. We present fully sampled high angular resolution two-dimensional kinematics in the Hα spectral line, optical and near-infrared imaging, as well as 21 cm atomic hydrogen data of the spiral galaxy NGC 278. This is a small non-barred galaxy, which has a bright star forming inner region of about 2 kpc in diameter, reminiscent of nuclear rings seen mainly in barred galaxies. The Hα kinematics show a disturbed velocity field, which may be partly the result of spiral density wave streaming motions. The 21 c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 34 publications
3
66
0
Order By: Relevance
“…HI its diameter is five times greater (Knapen et al 2004). Its dust-rich central parts are quite bright not only in the Hα line, but also in the infrared continuum (Dale et al 2000;Sanders et al 2003) and the [CII] line (Malhotra et al 2001) consistent with intense star-forming activity (Ho et al 1995;Eskridge et al 2002).…”
Section: Ngc 278 = Ddomentioning
confidence: 94%
“…HI its diameter is five times greater (Knapen et al 2004). Its dust-rich central parts are quite bright not only in the Hα line, but also in the infrared continuum (Dale et al 2000;Sanders et al 2003) and the [CII] line (Malhotra et al 2001) consistent with intense star-forming activity (Ho et al 1995;Eskridge et al 2002).…”
Section: Ngc 278 = Ddomentioning
confidence: 94%
“…But galaxies with molecular rings have been found that have no bars (e.g. NGC 278 & NGC 7217, Knapen et al 2004;Sarzi et al 2007). It has been shown that other physical properties, e.g., a weak oval distortion (Buta et al 1995), a dissolved bar (Verdes-Montenegro et al 1995), tidal effects of a companion galaxy (Combes 1988a), or a recent minor merger (Knapen et al 2004;Mazzuca et al 2006) can cause the same effect as a bar: the non-axisymmetric potential caused by the bar can channel gas to the nucleus, which is slowed down near or at the inner Lindblad resonance.…”
Section: "Wildfire" Vs Dynamicsmentioning
confidence: 99%
“…NGC 278 & NGC 7217, Knapen et al 2004;Sarzi et al 2007). It has been shown that other physical properties, e.g., a weak oval distortion (Buta et al 1995), a dissolved bar (Verdes-Montenegro et al 1995), tidal effects of a companion galaxy (Combes 1988a), or a recent minor merger (Knapen et al 2004;Mazzuca et al 2006) can cause the same effect as a bar: the non-axisymmetric potential caused by the bar can channel gas to the nucleus, which is slowed down near or at the inner Lindblad resonance. Elmegreen (1994) proposed a scenario in which the gravitational collapse of gas that is caught in an inner Lindblad resonance within a starburst ring, fueled by galactic bars or strong spiral arms, can lead to the formation of giant clouds with spots of intense star formation.…”
Section: "Wildfire" Vs Dynamicsmentioning
confidence: 99%
“…The non-barred nature of its host, NGC 7742, and the counterrotation observed in the central region might indicate that some past interactive event is responsible. For the similar non-barred nuclear ring host galaxy NGC 278, a past minor merger is indeed what we proposed as origin for its ring on the basis of the severely disturbed morphology and kinematics of its atomic gas (Knapen et al 2004). NGC 7742 has a companion galaxy, NGC 7743, but that seems too far away and of too regular morphology to be a candidate for a recent interaction.…”
Section: Physical Conditions Of the Gas: The Case Of Ngc 7742mentioning
confidence: 57%